2010
DOI: 10.1016/j.quageo.2009.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of oxygen plasma ashing as a pre-treatment for radiocarbon dating

Abstract: This study investigates the potential of low-temperature oxygen plasma ashing as a technique for decontaminating charcoal and wood samples prior to radiocarbon dating. Plasma ashing is demonstrated to be rapid, controllable and surface-specific, and clear differences are identified in the rate of ashing in different organic materials. However, the ability of plasma ashing to selectively remove these different components is limited in heterogeneous sample matrices. This is because oxidation is confined to the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 26 publications
(21 reference statements)
0
10
0
Order By: Relevance
“…In addition to the above three modification methods, modification methods such as low-temperature plasma [72,73], organic matter grafting [74], and ozone oxidation [32] have also been studied. Low-temperature plasma modification means that plasmas generated by glow, microwave, and corona were collided with C=C on the surface of biochar, and plasmas were oxidized to the oxygen-containing functional group, and enhanced the polarity of biochar [75].…”
Section: Other Modification Methodsmentioning
confidence: 99%
“…In addition to the above three modification methods, modification methods such as low-temperature plasma [72,73], organic matter grafting [74], and ozone oxidation [32] have also been studied. Low-temperature plasma modification means that plasmas generated by glow, microwave, and corona were collided with C=C on the surface of biochar, and plasmas were oxidized to the oxygen-containing functional group, and enhanced the polarity of biochar [75].…”
Section: Other Modification Methodsmentioning
confidence: 99%
“…It is thus preferable to perform pre-screening analyses to check that charcoal is relatively well preserved, and that no residual contaminant remains after the chemical pre-treatment. The need to develop novel sample preparation methods for radiocarbon analysis, through a better understanding of the charcoal structure subject to changes in environment and in-vitro has been recognized in recent publications (Bird et al, 2010). Other recent studies (Rebollo et al, 2008;Ascough et al, 2011) have shown that the chemical stability of fossil charcoal largely depends on the dissociation susceptibility of carboxyl groups in charcoal subject to pH changes in the environment and in-vitro.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, some alternative pretreatment methods for radiocarbon dating of charcoals have been proposed and are under development, e.g. hydrogen pyrolysis (HyPy) (Ascough et al, 2009(Ascough et al, , 2010, plasma ashing (Bird et al, 2010) and a wet oxidation/stepped combustion method (ABOx-SC) (e.g. Bird et al, 1999;Brock et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The instrument specification comparison shows that the power source used in the HPT‐100 in our study was 50 W lower than that of the POLARON PT7160 (Quorum Technologies, Laughton, UK) used for the previous organic matter removal experiment 38 . The lower power of the HPT‐100 generates a lower radio frequency (RF), which yields a lower oxidation potential 45 of O 2 + , O, O 2 , O − , 50 and electrons to react with the sample surface. Based on three temperature measurements, the working temperature inside the plasma chamber of our machine ranged between 65°C and 70°C after 30 min, 57°C and 60°C after 20 min, and 37°C and 43°C after 10 min.…”
Section: Methodsmentioning
confidence: 93%
“…In the field of conventional bulk isotope analysis, it has become common practice to perform a treatment to remove organic matter 32,37–44 . Low‐temperature oxygen plasma ashing (OPA) is widely used to remove organic matter from samples using ionized oxygen 38,45 with a working temperature of 60°C–70°C 46 . The effect of low‐temperature OPA treatment on the initial bulk isotopic composition has been demonstrated as being neglectable or within the limit of analytical error 44 .…”
Section: Introductionmentioning
confidence: 99%